I wonder why vultures are bald : and other questions about birds - O'Neill, Amanda (Danbury, Connecticut : Grolier Inc, 1999)
I Wonder Why Vultures Are Bald is jam-packed with fascinating facts about birds, from DO all birds sing?' to 'How do birds find their way?'.
Includes index
Keywords: Encyclopedias; Question and answers